Fault-bounded models of oil–Gas and gas–Hydrate accumulation in the Chaoshan Depression, the South China Sea - Guangjian, Zhong; Changmao, Feng; Yanlin, Wang; Shenghong, Chen; Ming, Sun; Hai, Yi; Junhui, Yu; Jing, Zhao; Zhongquan, Zhao (Frontiers in Earth Science, 2022)
The Dongsha Basin is a large Mesozoic basin extended from the northern South China Sea (SCS) to onshore the South China. Though long-term uplift and denudation since the end of the Mesozoic, there are still thick Mesozoic strata relict over the Dongsha waters where lies the largest depression, Chaoshan Depression. It was confirmed by a drilling hole, the well LF35-1-1, that there are high organic carbon-bearing marine Jurassic layers in the depression. However, the petroleum geology remains yet poorly understood in view of the deep basin structure, the Mesozoic hydrocarbon migration conditions and the oil-gas accumulation mechanism. In recent surveys, the seismic imaging quality has been significantly improved by employing long and quasi-3D seismic streamer techniques. Correlating with the regional geology onshore the South China, drilling data of the Well LF35-1-1 and well-tying seismic profiles, it is found that there are two sets of source rocks developed in semi-closed gulf during the Upper Triassic-Lower Jurassic and the Upper Jurassic. Their effective thicknesses are estimated as 495 m and 600 m respectively, being hopeful with high hydrocarbon generation potentials. During the Dongsha Movement occurred in the late Cenozoic, deep faults have been extensively activated to disturb the overlying sequences, even in some places break through the seafloor. A potential trap structure, DS-A, is found in an intra-sag bulge which is bounded by antithetic and synthetic faults. The oil and gas generated in the neighboring sags can migrate along the faults into reservoir layers at higher levels. The antithetic faults also play a role of seal for oil and gas from the hanging wall. Apparent flat bright spots appearing within the DS-A trap indicates likely entrapment of layered petroleum. The synthetic faults on the opposite side of the DS-A structure, although fails to seal oil-gas reservoirs, provide plumbing channels for oil and gas to leak to the shallow layers above which a few pockmarks and mud volcanoes are visible.It is likely for the leaked gas to form natural gas hydrates. A close cogenetic interrelation exists between the natural gas hydrates at the seafloor and oil-gas reservoirs in the deep.